Association of Liver Damage and Quasispecies Maturity in Chronic HCV Patients: The Fate of a Quasispecies - Josep Gregori; Marta Ibañez-Lligoña; Sergi Colomer-Castell; Carolina Campos; Damir García-Cehic; Josep Quer (Microorganisms)
Viral diversity and disease progression in chronic infections, and particularly how quasispecies structure affects antiviral treatment, remain key unresolved issues. Previous studies show that advanced liver fibrosis in long-term viral infections is linked to higher rates of antiviral treatment failures. Additionally, treatment failure is associated with high quasispecies fitness, which indicates greater viral diversity and adaptability. As a result, resistant variants may emerge, reducing retreatment effectiveness and increasing the chances of viral relapse. Additionally, using a mutagenic agent in monotherapy can accelerate virus evolution towards a flat-like quasispecies structure. This study examines 19 chronic HCV patients who failed direct-acting antiviral (DAA) treatments, using NGS to analyze quasispecies structure in relation to fibrosis as a marker of infection duration. Results show that HCV evolves towards a flat-like quasispecies structure over time, leading also to advanced liver damage (fibrosis F3 and F4/cirrhosis). Based on our findings and previous research, we propose that the flat-like fitness quasispecies structure is the final stage of any quasispecies in chronic infections unless eradicated. The longer the infection persists, the lower the chances of achieving a cure. Interestingly, this finding may also be applicable to other chronic infection and drug resistance in cancer.